Co-existing ulcerative colitis and takayasu arteritis: A case-based review - Karan Rajgopal Kalani; Anuj Achyut Ban; Sumeet Singla (Indian Journal of Rheumatology)
Both Takayasu arteritis (TAK) and ulcerative colitis (UC) are uncommon diseases with diverse pathophysiological and clinical features. Their occurrence in the same patient is highly unusual and interesting. We describe the case of a 32-year-old female with UC who developed TAK, 4 years after the initial diagnosis. She was also found to have the HLA subtype B52 which has been commonly reported in these two conditions. We discuss the similarities and differences in clinico-epidemiological, pathophysiological, and genetic features of TAK and UC. We also performed a literature search and reviewed similar case reports and case series of co-occurrence of TAK and UC, between 2010 and 2021.